Research progress on regenerative endodontic procedures - DAI Xingzhu; CHEN Lijuan; LIANG Yuee; ZHAO Wanghong (口腔疾病防治, 2023)
Regenerative endodontic procedures, based on dental pulp biology, use the basic principles of tissue engineering to promote the functional regeneration of dental pulp-dentin complexes. Good results have been achieved in the treatment of young permanent teeth with pulp necrosis or apical periodontitis. There have also been preliminary clinical explorations of the treatment of mature permanent teeth in recent years. The key to successful treatment is controlling infection as well as promoting tissue repair and regeneration. Moderate root canal mechanical preparation is allowed in the therapy of mature permanent teeth, while it is not recommended in the treatment of young permanent teeth. The choice of root canal irrigation and intracanal antisepsis requires a comprehensive consideration of the antibacterial effects, biological safety, and possible complications, such as crown discoloration and root canal calcification. The development of bioceramic materials provides more options for crown sealing materials, but further clinical evaluation is needed. In addition to traditional blood clot scaffolds, new types of tissue scaffolds represented by platelet-rich plasma, platelet-rich fibrin, concentrated growth factors and other platelet concentrates have been developed. Long-term and large-scale studies are needed to evaluate the actual clinical efficacy of these new scaffolds and the efficacy of their combined application with blood clots.